Atan Bina Hardware Sdn Bhd: It's expansion plan - Quoquab, Farzana; Mohammad, Jihad; Abdul Rahman, Ramzian; Mohd Sobri, Anis Makhillah; Yusof, Nadrah; Ibrahim, Ida Syahidah; Che Hussin, Chee Rohaya; Xia, Yang (2017)
It was early morning of 5th January, 2016. Nurul Zalikha (subsequently known as Nurul) was driving her car very fast to reach office before 8am. She had to attend one important meeting at 10am with her father Mr Ab. Rahim Bin Ab. Muthalib (subsequently known as Mr. Ab Rahim), the director of Atan Bina Hardware Sdn Bhd located at Masai, Johor Darul Takzim - West Malaysia.Atan Bina used to sell household hardware and construction materials.Nurul was driving and thinking about the discussion agenda.She whispered herself: Yes, I know that the sales is declining, but I also know that there will be a solution to this situation.We can't just postpone our expansion plan for this reason! Who knows, it might turn out to be a better option to boost up sales? May be our location is not strategic to attract the customers! May be we need to open different outlets in different places with better strategic location! We can't leave the situation like this... We must find way out to increase sales...